Development of low mass-transfer-resistance fluorinated TiO2-SiO2/PVDF composite hollow fiber membrane used for biogas upgrading in gas-liquid membrane contactor - Xu, Yilin (2019)
An inorganic-organic fluorinated titania-silica (fTiO2-SiO2)/polyvinylidene fluoride (PVDF) composite membrane was fabricated, via facile in-situ vapor-induced hydrolyzation method followed by hydrophobic modification. This low mass-transfer-resistance membrane, composing of a mesoporous layer deposited onto macroporous substrate, was designed for biogas upgrading in gas-liquid membrane contactor (GLMC) application. The surface hydroxylation was introduced to facilitate the bridging of TiO2-SiO2 nanoparticles and PVDF substrate, which resulted in a more coherent deposition of the fTiO2-SiO2 layer onto the substrate. The surface microstructure was fine-tuned by controlling the amount of doped Si precursor, forming an integrated mesoporous fTiO2-SiO2 layer. The resultant fTiO2-SiO2/PVDF composite hollow fiber membrane exhibited a tighter pore size of ~25 nm and a desired water contact angle of ~124°, which effectively prevented membrane wetting. The CO2 absorption fluxes of 8.0 and 5.6 × 10−3 mol m−2 s−1 were achieved due to the lower mass transfer resistance, by using 1 M of monoethanolamine (MEA) and sodium taurinate as absorbents with a liquid velocity of 0.25 m s−1, respectively. The long-term stability test showed a good integrity between the fTiO2-SiO2 layer and the PVDF substrate after 31-days of GLMC operation. The main benefit is the robust fluorinated inorganic layer which exhibited strong chemical resistance and high hydrophobicity, thus preventing membrane damage and pore wetting. Overall, this work provides an insight into the preparation of high–performance inorganic/organic composite hollow fiber membranes for carbon dioxide (CO2) removal in GLMC application.